Impact of Thyroid Autoimmunity on In Vitro Fertilization/Intracytoplasmic Sperm Injection Outcomes and Fetal Weight - Huang, Ning; Chen, Lixue; Lian, Ying; Wang, Haining; Li, Rong; Qiao, Jie; Chi, Hongbin (Frontiers in Endocrinology, 2021)
Several studies have reported the association between thyroid autoimmunity (TAI) and in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) outcomes.However, the findings remain controversial. We performed a large-scale retrospective cohort study to verify the effect of the presence of thyroid antibodies on IVF/ICSI outcomes and fetal growth and to evaluate the association between the types and titers of thyroid antibodies and adverse IVF/ICSI outcomes. A total of 16481 patients with infertility were referred to the Reproductive Center of Peking University Third Hospital for their first IVF/ICSI treatment between January 2018 and June 2019.Patients who sought IVF/ICSI treatment due to tubal or male factors infertility and who achieved fresh embryo transfer were included in our study. Finally, 778 patients with thyroid antibody positivity were selected as the TAI group, and 778 age-matched patients were included in the control group. The number of oocytes retrieved and high-graded embryos and the rates of clinical pregnancy, miscarriage, live birth, and preterm delivery were compared between the TAI and control groups. In addition, subgroup analysis was performed to demonstrate whether different types and titers of thyroid antibodies had different effects on IVF/ICSI outcomes. After adjusting for thyroid function, anti-Müllerian hormone levels, basal follicle stimulating hormone levels, basal estradiol levels and antral follicle count, the number of oocytes retrieved in the TAI group was significantly lower than that in the control group. No significant differences were observed between the two groups in the rates of clinical pregnancy, miscarriage, preterm delivery, live birth, and birth weight in singletons; however, the birth weight in twin pregnancy was significantly lower in the TAI group than in the control group. Subgroup analysis showed no association between the types or titers of thyroid antibodies and adverse IVF/ICSI outcomes. In conclusion, the presence of TAI in patients with infertility did not impair embryo quality or affect pregnancy outcomes, including clinical pregnancy, miscarriage, preterm delivery, and live birth. However, it decreased the number of oocytes retrieved and birth weight in twin pregnancy.